2022
DOI: 10.3390/ijerph191912484
|View full text |Cite
|
Sign up to set email alerts
|

Decision Tree-Based Foot Orthosis Prescription for Patients with Pes Planus

Abstract: Pes planus, one of the most common foot deformities, includes the loss of the medial arch, misalignment of the rearfoot, and abduction of the forefoot, which negatively affects posture and gait. Foot orthosis, which is effective in normalizing the arch and providing stability during walking, is prescribed for the purpose of treatment and correction. Currently, machine learning technology for classifying and diagnosing foot types is being developed, but it has not yet been applied to the prescription of foot or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…where W[A i ] represents the weights of i th feature, m is the process cycle, P(.) is the prior probability of C and di f f defines the distance for discrete features as Equation (2).…”
Section: Iterative Feature Selection and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…where W[A i ] represents the weights of i th feature, m is the process cycle, P(.) is the prior probability of C and di f f defines the distance for discrete features as Equation (2).…”
Section: Iterative Feature Selection and Classificationmentioning
confidence: 99%
“…Pes planus is a multidirectional deformity that occurs with the collapse of the medial longitudinal arch of the foot, valgus deformity of the heel, and forefoot abduction [1]. Its prevalence is between 20-37% in studies among healthy volunteers [2]. Pes planus can be developmental or acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed signi cant differences in calcaneal angle between normal foot and FFT with greater RCSP and maximum calcaneal eversion during gait and running [6,18,32] . The clinical treatment for correcting calcaneal eversion includes kinesio taping, athletic taping (AT) and foot-ankle orthoses [3,11,12,30,36] . In a meta-analysis, AT has been proven to be more effective than foot orthoses in controlling calcaneal eversion in FFT, which is characterised by convenient operation [7] .…”
Section: Introductionmentioning
confidence: 99%